Black, white and readable [nanochromics display]. - Perry, T.S.
The Irish company, Ntera Ltd., has developed an alternative to the LCD display. Called NanoChromics display (NCD), it features a stark, razor sharpness, with nearly black images on almost luminous, paper-white background. Text is easy to read in most lighting conditions, with a contrast ratio of 6:1 and a brightness of at least four times that of an LCD. NCD is also power-thrifty because its high contrast ratio eliminates the need for any kind of separate lighting systems and they do not need to be constantly refreshed unlike LCDs. In addition, NCDs can be manufactured on almost the entirely the same equipment used to manufacture LCDs. Hence, manufacturing cost of both display technologies are almost equal.
Keywords: Ireland; LCD; Ntera Ltd; Electronic display; High contrast ratio; Low-contrast flat-panel readouts; Nanochromics display; Viewing angle